Ionic Conductivity and Stability of the Lithium Aluminum Germanium Phosphate. (29th August 2016) - Cui, Yuantao; Rohde, Magnus; Reichmann, Thomas Ludwig; Mahmoud, Morsi M; Ziebert, Carlos; Seifert, Hans Jürgen
Abstract : Lithium aluminum germanium phosphate (LAGP) solid state electrolytes with different compositions were synthesized and then heat-treated at different temperatures. The ionic conductivity of the prepared samples was studied. Lithium ion cells using LAGP as solid state electrolyte were assembled and tested. The stability of the prepared LAGP samples was investigated.